Pengaruh Motivasi Dan Budaya Organisasi Terhadap Peningkatan Kinerja Personil Mabes Polri Melalui Kepuasan Kerja Sebagai Variabel Intervening - Yunus, Andi Hery Zulfikar; Daga, Rosnaini; Hatta, Moh. (Paradoks : Jurnal Ilmu Ekonomi, 2024)
The analysis method used is Path Analysis with SmartPLS software, aimed at depicting the actual state of the research object to understand the influence of motivation and organizational culture on the performance improvement of personnel at Mabes Polri through job satisfaction as an intervening variable by administering statements in a questionnaire to the personnel of Mabes Polri. The research findings indicate that (1) motivation has a positive and significant effect on job satisfaction of Mabes Polri personnel, (2) organizational culture has a positive and significant effect on job satisfaction of Mabes Polri personnel, (3) job satisfaction has a positive and significant effect on the performance of Mabes Polri personnel, (4) motivation has a positive and significant effect on the performance of Mabes Polri personnel, (5) organizational culture has a positive and significant effect on the performance of Mabes Polri personnel, (6) motivation has a positive and significant effect on the performance of Mabes Polri personnel through job satisfaction, and (7) organizational culture has a positive and significant effect on the performance of Mabes Polri personnel through job satisfaction. Motivation. It is the dominant variable affecting satisfaction. Work is 0.485 or 48.5%.